Early Pyrotechnology: The Evolution of the First Fire-Using Industries - Wertime, Theodore A. (1982)
contains chapters on ancient Near Eastern ceramics, soda-lime-silicate technology at Nuzi, pottery and faience in Mesopotamia, manufacture and use of burned lime plaster at Proto-Elamite Anshan, pyrotechnology and culture change at Tepe Hissar